The utility of neuro-QOL in idiopathic REM sleep behavior disorder - Daniel A. Barone; Harini Sarva; Natalie Hellmers; Fei Wang; Zhenxing Xu; Ana C. Krieger; Claire Henchcliffe (Sleep Science and Practice)
Abstract Introduction Idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD) can affect quality of life (QOL) for both patient and bed partner; has been less well-studied. Utilizing the Neuro-QOL, we aimed to investigate QOL complaints in subjects with iRBD, and whether QOL changes were associated with phenoconversion to neurodegenerative illness. Methods We prospectively enrolled subjects from the “REM Sleep Behavior Disorder Associations with Parkinson’s Disease Study (RAPiDS)” cohort and evaluated them via the NeuroQOL, both at baseline and then at follow-up evaluations. Determination of phenoconversion was ascertained from physical examination and medical chart review. Results Of those who completed both evaluations, there were 33 subjects with iRBD, with an average age of 61.9 ± 13.0 years, with 13 women and 26 men. Various QOL changes were found among those who phenoconverted versus those who did not; but following correction, none of these changes were significant. Conclusions This is the first time the Neuro-QOL has been studied in iRBD. QOL can be affected in this condition, but other screening tools will likely be needed for future studies.